A Contrastive Study of Shell Noun Use in English and Chinese Academic Articles - Liang Xiaorui (Ilmu Inovasi Nusantara, 2024)
A shell noun (SN) is a type of abstract noun whose pragmatic meaning is encapsulated within the context. The term